Analysis of the effect of temperature on creep resistance in nickel-based alloys used in gas turbines - Abdulhussein, Amenah Hamzah; Yasir, Mudher Naeem; Rahayf, Hadeel Abdul Hassan (Edelweiss Applied Science and Technology, 2024)
The investigation of the impact of temperature on creep resistance in nickel-based combinations is significant for optimizing the execution of gas turbines, where these materials are commonly utilized. Nickel-based amalgams are favored due to their amazing mechanical properties at tall temperatures, counting predominant creep resistance. Crawl is the time-dependent distortion of materials beneath consistent push, and it gets to be critical at lifted temperatures. This consider examines the relationship between temperature and creep resistance in nickel-based amalgams utilizing both hypothetical modeling and exploratory information examination. The creep rate is regularly depicted utilizing the Arrhenius-type condition, which relates temperature to the creep behavior of the fabric. MATLAB is utilized to demonstrate this relationship, perform reenactments, and analyze how varieties in temperature influence crawl resistance. The discoveries give experiences into the material’s execution at different working temperatures, empowering more successful fabric determination and turbine plan.